Bronchopneumonia associated with Mannheimia granulomatis infection in a Belgian hare (Lepus europaeus). (July 2017) - Britton, Ann P.; Redford, Tony; Zabek, Erin; Sojonky, Ken R.; Scouras, Andrea P.; Lewis, Danielle; Joseph, Tomy
Mannheimia granulomatis was first isolated from pneumonic European hares in the 1980s and has since been reported sporadically in pneumonic Swedish roe deer and Australian cattle. Although the pneumonic lesions caused by M. haemolytica in livestock have been extensively studied and reported, little is published with regard to the pneumonic lesions associated with M. granulomatis infection in any species. We describe the histopathology of purulent bronchopneumonia associated with M. granulomatis in a Belgian hare ( Lepus europaeus ) resident in British Columbia, Canada, and compare the lesions with those caused by M. haemolytica in livestock.